Public-private collaboration and risk transfer - González García, Julio (2021)
The study analyses the implications of implementing the principle of budgetary stability on the clauseing of public-private partnership mechanisms. In particular, how to set up adequate risk-sharing and especially how public supports are structured can determine that compute as a public deficit for the purposes of Eurostat’s SEC 95 doctrine.